The Optimization of Budget Outcome to Create Trust in Public Expenditure Allocation on Local Budget - Koeswara, Hendri (Research and Development Agency Ministry of Home Affairs, 2016)
Planning and budgeting process is the most crucial process in the administration of local government. Results of previous studies in Solok, the increase in the total budget is not accompanied by spending management capabilities. Expenditure of public service has always fluctuated, but ideally should always increasing. This study aimed to analyze the outcome of the budget in the allocation of public spending in an effort to realize the presence of trust on the budget in Solok West Sumatra Province. This study uses qualitative research methods with the type of research that is selected using descriptive type. While the techniques of data collection are done through an interview, observation and documentation study. This study further highlights the emic perspective, is the voice of the informant, not the personal opinion of the researchers (etic). Then, the data analysis is done categorically and chronologically, viewed repeatedly, and will continue to be encoded. To test the verification of data, triangulation is done by comparing the results of interviews with documents obtained in the field and testing of concepts used by researchers with the information given by the informant. The results showed that the pathology was found that budget allocations reflect inefficiencies as a failure of the link between policy, planning, and budgeting as a fragmented system. But on the other hand, it must be admitted there has been â€œtrustâ€ among policymaking actors in allocating public expenditure budget in playing the role in the budget policy.